2017
DOI: 10.1186/s12969-017-0176-y
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in transitioning adolescents and young adults with rheumatologic diseases to adult Care in a Developing Country - the Brazilian experience

Abstract: BackgroundTransition guidelines and recommendations for developing countries are limited and best transition practices in young patients with chronic medical conditions have been poorly examined. This study evaluates transition practices from pediatric to adult rheumatology care in Brazil.MethodsPracticing pediatric rheumatologists registered in the Brazilian Society of Rheumatology were e-surveyed with SurveyMonkey® using the Chira et al. questionnaire that had been used previously to evaluate transition prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 19 publications
0
26
0
4
Order By: Relevance
“…Well-established transition programs are still a challenge in LA clinical practice. A recent survey to assess transition practices in Brazil showed that only 14% of the pediatric rheumatologists were satisfied with their current transition process [39].…”
Section: Discussionmentioning
confidence: 99%
“…Well-established transition programs are still a challenge in LA clinical practice. A recent survey to assess transition practices in Brazil showed that only 14% of the pediatric rheumatologists were satisfied with their current transition process [39].…”
Section: Discussionmentioning
confidence: 99%
“…No país, a discussão sobre transição de cuidados da pediatria para a medicina de adultos ainda é incipiente, com raros trabalhos de especialidades pediátricas, que ainda não caracterizam a utilização de protocolos institucionais. 24,25 Este não é um problema apenas dos países de língua portuguesa, porém. A discussão nos Estados Unidos, por exemplo, já avança há 20 anos aproximadamente, com o primeiro consenso sobre transição (Academia Americana de Pediatria/Academia Americana de Médicos de Família/Colégio Americano de Médicos/Sociedade Americana de Medicina Interna) datado de 2002.…”
Section: Resultsunclassified
“…Some of the pediatric patients included in our study were approaching adulthood. The transfer between pediatric and adult care for patients with rheumatic disease can be complex and has been shown to lead to an increase in active disease in 30% of patients [4951]. The importance of uninterrupted care has led the American College of Rheumatology to develop a tool kit for healthcare professionals aimed at facilitating transition of patients through this potentially difficult period [52].…”
Section: Discussionmentioning
confidence: 99%